2009
DOI: 10.1002/crat.200900435
|View full text |Cite
|
Sign up to set email alerts
|

Solutocapillary convection in germanium‐silicon melts

Abstract: Surface tension gradients in free crystal growth melts give rise to convective flow. If these gradients are due to thermal gradients, the well known thermocapillary (Marangoni) convection ensues. Concentration gradients due to segregation at the interface during growth can lead to additional solutocapillary convection. A system with large solutocapillary convection is Ge-Si due to the pronounced segregation and the strong difference in surface tension; solutal buoyancy convection is also present due to the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Schwabe (2007) proposed a method to make dopants or impurities incorporate in the crystal by controlling the interaction of solutocapillarity and thermocapillarity deliberately. This feasibility has been proved by experimental investigations of solutocapillary convection (Cröll et al 2009;Arafune et al 2011;Schwabe et al 1996), numerical simulations (Abbasoglu and Sezai 2007;Minakuchi et al 2014;Lyubimova et al 2011) and linear stability analysis (Lyubimova 2007). As demonstrated experimentally by Cröll et al (2009) in a shallow rectangular crucible under microgravity, the measured velocity of the tracers is up to 55 mm/s at the onset of crystallization.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Schwabe (2007) proposed a method to make dopants or impurities incorporate in the crystal by controlling the interaction of solutocapillarity and thermocapillarity deliberately. This feasibility has been proved by experimental investigations of solutocapillary convection (Cröll et al 2009;Arafune et al 2011;Schwabe et al 1996), numerical simulations (Abbasoglu and Sezai 2007;Minakuchi et al 2014;Lyubimova et al 2011) and linear stability analysis (Lyubimova 2007). As demonstrated experimentally by Cröll et al (2009) in a shallow rectangular crucible under microgravity, the measured velocity of the tracers is up to 55 mm/s at the onset of crystallization.…”
Section: Introductionmentioning
confidence: 86%
“…This feasibility has been proved by experimental investigations of solutocapillary convection (Cröll et al 2009;Arafune et al 2011;Schwabe et al 1996), numerical simulations (Abbasoglu and Sezai 2007;Minakuchi et al 2014;Lyubimova et al 2011) and linear stability analysis (Lyubimova 2007). As demonstrated experimentally by Cröll et al (2009) in a shallow rectangular crucible under microgravity, the measured velocity of the tracers is up to 55 mm/s at the onset of crystallization. Arafune and Hirata (1999) found that the surface velocity of solutocapillary flow is 3-5 times larger than that of the thermocapillary flow in In-Ga-Sb system in a rectangular open boat.…”
Section: Introductionmentioning
confidence: 86%
“…According to Cröll et al [86], such mixed convection is explained below. According to Cröll et al [86], such mixed convection is explained below.…”
Section: Bridgman Edge-defined Film-fed and Othermentioning
confidence: 96%
“…Cröll et al [86] carried out the directional solidification experiments of Ge x Si 1Àx mixtures of different compositions between 3% and 9% Si under microgravity condition during a parabolic flight campaign, where the samples of 2-3 mm in depth poured in a SiC-coated graphite crucible (inside dimensions 15 Â 30 mm 2 ) were heated by a doubleellipsoid mirror furnace whose two lamps were focused onto one end of the crucible. Figure 22.29 shows the three different experimental stages with a schematic view of the convective flow and the position of tracers put to visualize the flow direction of the solutocapillary flows: (a) the sample is completely melted by equally heating from both sides, and the cold spot is in the crucible center leading to two opposing thermocapillary convective rolls, (b) completely molten sample is reduced heating from the right side, and consequently the cold spot moves near the crucible wall, leading to a much reduced thermocapillary convective roll on the right, and (c) solidification starts from the right side, and solutocapillary flow caused by the concentration gradient along the surface due to segregation pushes the tracers away from the melt/crystal interface, where solutocapillary convection opposes thermocapillary convection in the Ge x Si 1-x system since Si, having the higher surface tension, is preferentially incorporated into the crystal during growth.…”
Section: Bridgman Edge-defined Film-fed and Othermentioning
confidence: 99%
“…For the compound semiconductor crystal growth, the coupling thermal and solutocapillarybuoyancy effects in the mixture are rather more complex than that of pure fluid. Cröll et al [38] conducted an experiment during the parabolic flight campaign to separate the buoyancy effect from the capillary convection. The solutocapillary convection was conclusively observed during the solidification of silicon-germanium.…”
Section: Introductionmentioning
confidence: 99%